Mechanical circulatory support in the management of life-threatening arrhythmia. Issue 8 (31st December 2020) - Della Bella, Paolo; Radinovic, Andrea; Limite, Luca Rosario; Baratto, Francesca
Abstract: Life-threatening refractory unstable ventricular arrhythmias in presence of advanced heart failure (HF) may determine haemodynamic impairment. Haemodynamic mechanical support (HMS) in this setting has a relevant role to restore end-organ perfusion. Catheter ablation (CA) of ventricular tachycardia (VT) is effective at achieving rhythm stabilization, allowing patient's weaning from HMS, or bridging to permanent HF treatments. Acute heart decompensation during CA at anaesthesia induction in presence of advanced heart disease, in selected cases requires a preemptive HMS to prevent periprocedure adverse outcomes. Substrate ablation during sinus rhythm (SR) might be an effective strategy of ablation in presence of unstable VTs; however, in a minority of patients, it might have some limitations and might be unfeasible in some settings, including the case of the mechanical induction of several unstable VTs and the absence of ablation targets. In case of the persistent induction of unstable VTs after a previous failure of a substrate-based ablation in SR, a feasible alternative strategy of ablation might be VT activation/entrainment mapping supported by HMS. Multiple devices are available for HMS in the low-output states related to electrical storm and during CA of VT. The choice of the device is not standardized and it is based on the centres' expertise. The aim of this article is to provide an up-to-date review on HMS for the management of life-threatening arrhythmias, in the context of catheter ablation and discussing our approach to manage critical VT patients.